THE POSSIBLE EFFECTS OF THE EU ACCESSION ON THE WESTERN BALKANS AGRICULTURAL TRADE - Mizik, Tamás; Meyers, William (Economics of Agriculture, 2013)
The quickest accession to the European Union is a shared, short term goal of the Western Balkan countries (Albania, Bosnia and Herzegovina, the Former Yugoslav Republic of Macedonia and Montenegro, while Croatia has already accessed). It will cause remarkable changes on their agricultural sector and therefore on their agricultural trade. In order to evaluate the possible effects of the accession, the present situation of agriculture should be analysed. This paper gives an overview of the Western Balkan countries agriculture (agricultural value added, agricultural employment, agricultural production and its structure) and its trade relations (major trade partners, major products, trade balance,) and discusses the potential impact that adoption of EU domestic agricultural and trade policy would have on the sector. The experience of other new member states from Central and Eastern Europe shows that price, production and trade can change significantly after accession as well as during the pre-accession period. How much of this adjustment occurs before or after accession depends on the pre-accession policy and market adjustments. Finding niche markets or being cost competitive are crucial tasks for these countries during the accession process.